New records algal species from the Shatt Al-Arab River, Southern Iraq - Alwaeli, Aqeel A.; Athbi, Ahmed M. (Mesopotamian Journal of Marine Sciences, 2021)
Shatt Al-Arab River is an important inlands river in Iraq, It is considered an important source of fresh and water for the city of Basrah, as it is used for drinking and orchards irrigation also used for industrial and commercial purposes. Sampling was carried out monthly from November 2019 to December 2020 from Shatt Al-Arab River. The present study made records nine of algae species for the first time in Iraq. Represented by six species of Chlorophyta (Eremosphaera tanganyikae, Microspora wittrockii, Monoraphidium komarkova, Mychonastes pusshpae, Scenedesmus similagineus and Spongiococcum tetrasporum), one species of Cyanophyta (Pseudanabaena catenata), one species of Dinophyta (Impagidinium paradoxum), and one species of Euglenophyta (Strombomonas verrucosa).